2001
DOI: 10.1046/j.1365-3083.2001.00856.x
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Heterogeneity, Antigen Presentation, and Membrane Fluidity: Implications in Visceral Leishmaniasis

Abstract: Morphological and functional heterogeneity of the splenic macrophage (Mf) population was studied in Leishmania donovani (LD) infected BALB/c mice. On a discontinuous percoll gradient two distinct Mf populations were separated. They differed significantly in size as evident from Scanning Electron Microscopy (SEM). Morphologically, the bigger Mf (LM) showed surface projections, whereas the smaller Mf (SM) was round. As regards the antigen-presenting abilities, the LM of infected animals showed defective antigen-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 47 publications
1
21
0
Order By: Relevance
“…Previously, we have demonstrated that a subset of splenic M of Leishmania-infected BALB/c mice display an increase in membrane fluidity coupled with defective Ag-presenting function; this inability to present Ag was not due to the lack of peptide-MHC complex formation on the surface of M (11). The present work demonstrates for the first time that during their intracellular life cycle, Leishmania parasites disrupt the membrane raft of M by increasing membrane fluidity.…”
supporting
confidence: 56%
See 1 more Smart Citation
“…Previously, we have demonstrated that a subset of splenic M of Leishmania-infected BALB/c mice display an increase in membrane fluidity coupled with defective Ag-presenting function; this inability to present Ag was not due to the lack of peptide-MHC complex formation on the surface of M (11). The present work demonstrates for the first time that during their intracellular life cycle, Leishmania parasites disrupt the membrane raft of M by increasing membrane fluidity.…”
supporting
confidence: 56%
“…Previously we demonstrated that a subset of splenic M of LD-infected BALB/c mice showed increased membrane fluidity and defective Ag-presenting ability (11). The question arises of whether the rigidity of the membrane lipid bilayer is a critical determinant of the Ag-presenting ability of M in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Internalization involves interaction between the parasite and the plasma membrane of the cell host 36,55,56 . Low cholesterol levels in humans decrease the number of circulating lymphocytes, thus increasing the chances of mortality 23,34 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to playing an important role in the maintenance of membrane fl uidity, cholesterol is essential for the proper function of antigen presenting cells and is also a prognostic indicator of increased morbidity and mortality associated with pathological conditions [34][35][36] . This lipid is responsible for the formation of membrane rafts, which are essential for Leishmania entry [37][38][39] .…”
Section: Methodsmentioning
confidence: 99%
“…Thus, CD28 signaling is not required for inducing MTOC reorientation under these conditions, probably reflecting the lower activation threshold and relative costimulation independence of effector T cells (3). Finally, it has recently been reported that Leishmania-infected macrophages display altered membrane fluidity, with changes in the distribution and activity of membranous projections (41). However, macrophage membrane mobility also did not appear to be necessary for activating T cells for a MTOC response, as prefixation of macrophages with paraformaldehyde had no effect on this event (Fig.…”
Section: Mtoc Reorientation Requires a Higher Threshold Of Tcr Stimulmentioning
confidence: 80%